Auditoría de cumplimiento tributario en la cooperativa de ahorro y crédito pushak runa en el periodo 2016. - Arias Gonzalez, Alexandra Paulina (2018)
The present research work is a TAX COMPLIANCE AUDIT IN THE PUSHAK RUNA SAVINGS AND CREDIT COOPERATIVE IN THE 2016 PERIOD with the objective of evaluating the process and tax compliance that the entity has had in the aforementioned period. Chapter I, makes reference to the Reference Framework; where the problem of research work is detailed, the objectives that are going to be obtained. Chapter II corresponds to the Theoretical Framework; in which the structure of the entity is described, its history and other generalities, definitions of Tax Audit, its phases, normative framework, and formal duties. Chapter III, describes the Methodological Framework; used in the examination, technical methods and research instruments, population and sample. Chapter IV, includes the Results and Discussion; which applies the phases together with the Tax Audit processes. Chapter V presents the findings of the Audit which also includes the conclusions and recommendations that are addressed to the cooperative's officials.